Measuring phased‐array antenna beampatterns with high dynamic range for the Murchison Widefield Array using 137 MHz ORBCOMM satellites. Issue 7 (6th July 2015) - Neben, A. R.; Bradley, R. F.; Hewitt, J. N.; Bernardi, G.; Bowman, J. D.; Briggs, F.; Cappallo, R. J.; Deshpande, A. A.; Goeke, R.; Greenhill, L. J.; Hazelton, B. J.; Johnston‐Hollitt, M.; et al.
Abstract Detection of the fluctuations in a 21 cm line emission from neutral hydrogen during the Epoch of Reionization in thousand hour integrations poses stringent requirements on calibration and image quality, both of which necessitate accurate primary beam models. The Murchison Widefield Array (MWA) uses phased‐array antenna elements which maximize collecting area at the cost of complexity. To quantify their performance, we have developed a novel beam measurement system using the 137 MHz ORBCOMM satellite constellation and a reference dipole antenna. Using power ratio measurements, we measure the in situ beampattern of the MWA antenna tile relative to that of the reference antenna, canceling the variation of satellite flux or polarization with time. We employ angular averaging to mitigate multipath effects (ground scattering) and assess environmental systematics with a null experiment in which the MWA tile is replaced with a second‐reference dipole. We achieve beam measurements over 30 dB dynamic range in beam sensitivity over a large field of view (65% of the visible sky), far wider and deeper than drift scans through astronomical sources allow. We verify an analytic model of the MWA tile at this frequency within a few percent statistical scatter within the full width at half maximum. Toward the edges of the main lobe and in the sidelobes, we measure tens of percent systematic deviations. We compare these errors with those expected from known beamforming errors.